Stone/tissue differentiation for holmium laser lithotripsy using autofluorescence. Issue 9 (22nd September 2015) - Lange, Birgit; Cordes, Jens; Brinkmann, Ralf
<x xml:space="preserve">Abstract</x> Background and Objectives Holmium laser lithotripsy is a safe and effective method to disintegrate urinary stones of all compositions in an endoscopic procedure. However, handling and safety could be improved by a real‐time feedback system permanently monitoring the position of the treatment fiber. The laser is fired only when the fiber is identified as being placed in front of stone. This work evaluates the potential of fluorescence detection with an excitation wavelength of 532 nm for this purpose. Materials and Methods A fiber‐based fluorescence measurement was set‐up to acquire autofluorescence signals from several human renal calculi, artificial stones, and porcine tissue samples (renal calix and ureter). Three different approaches were investigated. First, experiments were performed with a pulsed laser source with a wavelength of 532 nm, pulse energy 36.5 ± 1 μJ, pulse duration 1.2 ± 0.5 nanoseconds, and a repetition rate of 1 kHz with 15 urinary concretions. In the second step, a series of measurements on 42 human urinary calculi samples was carried out using low power continuous wave excitation of 0.4 ± 0.1 mW. Fluorescence was also measured simultaneously to stone fragmentation by holmium laser pulses (pulse energy 240 ± 50 mJ, repetition rate 10 Hz). Finally, a modulated excitation/detection scheme (lock‐in technique) was implemented to render fluorescence detection insensitive to white background light. Results Unlike porcine renal calix, ureter, and artificial stone human urinary calculi show a strong fluorescence signal when excited with 532 nm. With pulsed excitation on urinary stone (20, 000 ± 11, 000) counts were registered at 587 nm with the CCD‐array of a grating spectrometer in an integration time of 50 milliseconds. Tissue gave lower count rates of ≤(5, 500 ± 1, 100) even with longer integration times (500 milliseconds/1 second). With a cw excitation power of 0.4 mW (13, 000 ± 11, 000) counts were registered in an integration time of 200 milliseconds at 587 nm (porcine renal calix: (770 ± 340)). Modulated excitation (66 Hz) with an average power of 0.3 mW and detection with a photodiode resulted in a lock‐in amplifier signal of 1.5–4.3V on stone (background and skin: <0.5V). Conclusion With the lock‐in technique, autofluorescence from stones can be detected with only the average excitation power of a green aiming beam overlaid to the Ho:YAG‐laser beam (power ≤ 1 mW). Since tissue shows very little autofluorescence when excited with 532 nm, this fluorescence signal enables monitoring of the correct position of the treatment fiber during ureteroscopic procedures. Lasers Surg. Med. 47:737–744, 2015. © 2015 Wiley Periodicals, Inc.